Business analysis for practitioners : a practice guide. (Project Management Institute, Inc, 2024)
"Business Analysis for Practitioners: A Practice Guide - Second Edition makes business analysis accessible in your professional and daily life, helping you apply business analysis skills to solve problems. You'll learn the context, environment, and practice of business analysis that can lead to successful outcomes. Use this guide to embrace a business analysis mindset for successful investigation and discovery-and as a tool to achieve outcomes. Adopting this mindset can help you develop an openness to questioning, learning, and solution options that are the core of business analysis work. The guide can also assist you in developing a free and open flow of communication and ideas, creating a platform for organizational prosperity. This rich publication provides a sound basis for business analysis to deliver a positive impact on your project success rates"-- Provided by publisher.
Keywords: Project management.; Business planning.; Management.; elektronické knihy; electronic books